A novel lncRNA PTTG3P/miR-132/212-3p/FoxM1 feedback loop facilitates tumorigenesis and metastasis of pancreatic cancer - Liu, Wenyu (Cell Death Discov, 2020)
Pseudogene pituitary tumor-transforming 3 (PTTG3P) is emerging as a key player in the development and progression of cancer. However, the biological role and clinical significance of PTTG3P in pancreatic ductal adenocarcinoma (PDAC) remain unclear. Here, we found that PTTG3P was significantly upregulated in PDAC tissues. Elevated PTTG3P expression correlated with larger tumor size and worse differentiation, and reduced overall survival. Bioinformatics and experimental evidence revealed that PTTG3P promoted malignant phenotypes and FoxM1 signaling pathway in PDAC cells. Mechanistically, PTTG3P functions as a microRNA sponge to positively regulate the expression of FoxM1 through sponging miR-132/212-3p. Moreover, it showed that FoxM1 transcriptionally activated PTTG3P expression, thus forming a feedback loop to promote the aggressiveness of PDAC cells. Taken together, our findings suggest that PTTG3P promotes PDAC progression through PTTG3P/miR-132/212-3p/FoxM1 feedforward circuitry and it may serve as a promising diagnostic marker or target for treatment in PDAC patients.